Nura, Megi Hedian The Role Of Corporate Social Responsibility (CSR) In Mediate The Effect Of Corporate Governance (CG) On Financial Performance: PERAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM MEMEDIASI PENGARUH CORPORATE GOVERNANCE (CG) TERHADAP KINERJA KEUANGAN - Megi Megi Hedian Nura; Abel Tasman (Universitas Negeri Padang, 2023)
This study aims to analyze the effect of (1) Corporate Governance on Corporate Social Responsibility, (2) Corporate Governance on Financial Performance, (3) Corporate Social Responsibility on Financial Performance, (4) Corporate Social Responsibility (CSR) has a role in mediating the relationship between Corporate Governance (CG) on Financial Performance listed on the Indonesia Stock Exchange in 2015-2021. Sample of 26 companies was obtained with 182 observational data for each variable. Structural Equation Modeling (SEM) Assumptions Test Method using the Amos 22 program. The results of this study conclude that (1) Corporate Governance (CG) has an influence and is significant on Corporate Social Responsibility (CSR) (2) Corporate Governance (CG) has an influence and is significant on financial performance, (3) Corporate Social Responsibility (CSR) has significant and significant effect on Financial Performance, and (4) Corporate Social Responsibility (CSR) has a role of mediating the relationship between Corporate Governance (CG) on Financial Performance.